الخلايا الجذعية قانوناً وشرعاً - دراسة تحليلية: Stem Cells Legally and Legally: An Analytical Study - Al Abdouli, Juma Saeed Ahmed Ali; Bin Abdul Majid, Mohd Nasir (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث شهد العصر الحاضر تقدما هائلاً في مجال الطب البشري الإنساني، وأصبحت عمليات نقل الخلايا الجذعية من إنسان لآخر ممكنة، وهنالك خلافات فقهيه في نقلها، فمنها من أجازت ذلك لمريض محتاج ومنها ما منعته إلا بشروط محددة، ومن هذا المنطلق تتجه العديد من الدراسات والأبحاث الطبية على قبول استخدام الخلايا الجذعية الجينية في الجوانب العلمية والطبية المختلفة، وبالتالي أدى تطورها في العصر الحديث إلى ظهور العديد من المشكلات في مختلف دول العالم نتيجة لعدم وجود قوانين تنظم وتحكم المسألة الطبية والفقهية في الخلايا الجذعية، وصولاً للنتائج الدراسات أو العلاجات الطبية الحديثة ، حيث تكمن أهمية دراستها لتلك للدول التي لم تنظر لهذا التطور في استخدام الخلايا الجذعية بعد، والعمل إلى إقتراح حلول مناسبة والمنظمات الطبية الدولية من خلال توضيح خطرها و القدرة على سن التشريعات اللازمة والمناسبة. ABSTRACT Stem cells are the raw material of the body. They are the generative cells for all other cells that perform specialized functions. Stem cells divide to form more cells and are called daughter cells in the body or in the laboratory under appropriate conditions. These daughter cells either become new stem cells or become specialized cells (differentiated) with another, more specialized function, such as blood cells, brain cells, heart muscle cells, or bone cells. Other cells in the body do not have this natural ability to generate new types of cells. The rapid development in experiments and research on adult stem cells has led to a legal gap between the development in research and the regulation of laws that govern this development, as the technical and scientific development and the development of methods and means of treatment with adult stem cells has not been followed by a development in laws, so it became It is necessary to resort to legal specialists in the development of legislative texts, and the laws that regulate this. In light of the foregoing, it is clear that the success of the medical work of some countries in the use of stem cells is based, whether or not, on the enactment of appropriate laws and adherence to jurisprudential opinions, and the obligations imposed on them, in order to preserve the harm that may be caused to others.